The effect of Dipyridamole on transient ischemia - reperfusion injury of the liver - İbrahim ELVERDİ,; Sadık ERSÖZ,; Zeki DÖŞEYEN,; Esra ERDEMLİ,; Uğur BENGİSUN,; Ethem GEÇİM,; Nusret ARAS, (Turkish Journal of Gastroenterology, 2019)
-